Kemas Ulang Informasi Songket Pandai Sikek Minangkabau - Putri, Widya; Desriyeni, Desriyeni (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2019)
AbstractThe writing of this paper discussesÂ repackaging information on Â SongketÂ Pandai Sikek Minangkabau. The purpose of this paper is to describe the repackaging of Songket Pandai Sikek Minangkabau information. This type of research is qualitative with descriptive methods. Data collected through observation and interviews with the owners of the Songket Pandai Sikek Crafts, craftsmen, employees of the Songket Pandai Sikek souvenir shop, and buyers of the Pek Sikek Songket. Based on the discussion it was concluded that the stages of making repackaging information on Songket Pandai Sikek Minangkabau, as follows: 1) identifying user needs; 2) information gathering; 3) packaging information, including cover, preface, table of contents, core discussion and cover; 4); determine the target audience; 5) product evaluation and manufacturing process.Keywords: repack, pandai sikek, Minangkabau